Logistic model for adherence to ministry of health protocols and guidelines by public transport vehicles in Kenya during COVID-19 pandemic - Kiptum, Kiprotich Clement (Engineering and Applied Science Research, 2021)
To know whether a given public transport vehicle will observe COVID-19 Ministry of Health Protocols and Guidelines in Kenya, a logistic expression was developed based on gender, type of vehicle, distance covered and the possibility of contracting COVID-19 by passengers while on board a given vehicle. Data collection was done by use 112 questionnaires administered on line. The respondents were first year students attending online courses in Kenyan University. Results showed majority of the respondents (41%) used 8-seater vehicle to travel. As for the distance travelled, majority of the respondents (37.3%) covered less than 25 km to reach their home County Headquarters. Possibility of infection in 8-seater and 32-seater vehicle was concentrated in level 3 while that for 14-seater was concentrated in Level 4. For 45-seater and 63-seater vehicles the possibility of infection was in level 2. A model efficiency of 84.8% was found indicating that the model is good. The results of this study provided information on behaviour of public transport sector in Kenya.